INTEGRATING DIGITAL TECHNOLOGIES IN VISUAL ARTS EDUCATION TO ENHANCE STUDENTS’ CREATIVE AND AESTHETIC SKILLS - Boboniyozova Roziya Mirsalim qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article examines the integration of digital technologies in visual arts education and its impact on students’ creative and aesthetic skills. The study highlights methods such as virtual galleries, 3D modeling, digital drawing platforms, and interactive multimedia, which facilitate independent learning, artistic experimentation, and aesthetic appreciation. Drawing upon research by Shovdirov S.A. and other scholars, the article demonstrates how digital technologies transform visual arts lessons into engaging, student-centered learning environments that enhance creativity, critical thinking, and artistic competence.